2017
DOI: 10.1177/0300060517731952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of activated clotting times measured using the Hemochron Jr. Signature and Medtronic ACT Plus during cardiopulmonary bypass with acute normovolemic haemodilution

Abstract: ObjectiveThis study compared the activated clotting time (ACT) measured using the Hemochron Jr. Signature (HACT) with the ACT measured using the Medtronic ACT Plus (MACT) during cardiopulmonary bypass (CPB) with acute normovolemic haemodilution (ANH) in patients undergoing cardiac surgery.MethodsThe ACT was checked at baseline with both devices after inducing anaesthesia, and 400 to 800 mL of whole blood was withdrawn to induce moderate ANH. Before initiating CPB, a 300-IU/kg bolus dose of heparin was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Assuming a statistical power of 80% to reach an alpha level of 5%, the needed sizing of each group would be 15 patients to discover a difference of 300 mL in blood loss between groups, considered to be a clinically significant difference. Previous studies 2,14 have shown that assuming a blood loss variability of 300 mL is reasonable. R (Version 3.5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assuming a statistical power of 80% to reach an alpha level of 5%, the needed sizing of each group would be 15 patients to discover a difference of 300 mL in blood loss between groups, considered to be a clinically significant difference. Previous studies 2,14 have shown that assuming a blood loss variability of 300 mL is reasonable. R (Version 3.5.…”
Section: Discussionmentioning
confidence: 99%
“…ACT was measured before and during CPB with high range ACT kaolin cartridges (Medtronic ACT Plus ® System). 14 Blood sampling was drawn from the patients’ arterial line or from the CPB circuit. After weaning of bypass and protamine reversal, a high-range heparinase test cartridge (Medtronic ACT Plus System) was used in addition to ACT to determine any residual heparin in the blood.…”
Section: Methodsmentioning
confidence: 99%
“…Without aprotinin, baseline celite measurements before heparinization tend to be 10% higher than those of kaolin tests, while kaolin ACT values generally exceed those of celite-based tests during CPB (10). However, baseline ACT+ values are approximately 20% lower than those of standard celite ACT tests and this difference seems to persist during full heparinization for cardiac surgery in comparison with both kaolinand celite-activated tests (11)(12). This suggests that the combination of the three activators in the ACT+ test can initiate the intrinsic coagulation cascade more rapidly than celite or kaolin alone.…”
Section: Discussionmentioning
confidence: 99%
“…Because a significant variability in ACT values has been reported between different brands of ACT devices findings cannot be extrapolated on a 1:1 basis to institutions using different brands of ACT devices and different type of cartridges to perform the measurements. [25][26][27][28] For the current study we used the Hemostatis Management System Plus (HMS Plus, Medtronic Inc. ® , Minneapolis, MN, USA). Besides the ACT, the HMS Plus also estimates heparin dose and heparin dose response.…”
Section: Discussionmentioning
confidence: 99%